Nonlinear dynamical model for a cancer cell death - Cardenas-Garcla, Maura; Areola Flores, Jesus Andres (JOURNAL OF ADVANCES IN BIOLOGY, 2016)
The nonlinear biochemical processes and feedback play a crucial role in the physiology of living organism; they are powerful tools that allow us to understand the complex biochemical processes and their dynamics. Nonlinear biochemistry has been used to explain the mechanism of regulation of thyroid hormone, the Krebs cycle and blood pH. Another example of such tools is the process of cell death in various forms. There are mathematical models, which show the dynamics of protein synthesis in the cell; such models demonstrate the nonlinearity of the mechanism showing how the concentration of intracellular and extracellular proteins varies depending on metabolic needs of the cell. These models can be used to describe the dynamics of different biochemical mechanisms involved in cell death. In particular, in this paper we employ nonlinear dynamics to model in a closed system two cells, one normal and one cancerous.